2012
DOI: 10.1016/j.ajpath.2012.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Acute Oral Ethanol Exposure Triggers Asthma In Cockroach Allergen–Sensitized Mice

Abstract: Asthma may be triggered by multiple mediators, including allergen-IgE cross-linking and non-IgE mechanisms. Several clinical studies have shown acute ethanol consumption exacerbates asthma, yet no animal model exists to study this process. We developed a model of ethanol-triggered asthma in allergen-sensitized mice to evaluate the mechanisms of ethanol inducing asthma-like responses. Outbred mice were exposed to cockroach allergens on Days 0 and 14; and on Day 21, mice received ethanol by oral gavage. Tracer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 55 publications
1
12
1
1
Order By: Relevance
“…First alcohol may influence immunology, or conversely the altered immunology in chronic airway diseases may cause the respiratory reactions upon exposure to alcohol. Several studies propose alcohol could cause eosinophilic inflammation or induce IgE supporting the first possibility . The latter hypothesis is analogous to reports in NERD, suggesting respiratory mucosal inflammatory disease could be the underlying mechanism in aspirin hypersensitivity .…”
Section: Discussionsupporting
confidence: 58%
“…First alcohol may influence immunology, or conversely the altered immunology in chronic airway diseases may cause the respiratory reactions upon exposure to alcohol. Several studies propose alcohol could cause eosinophilic inflammation or induce IgE supporting the first possibility . The latter hypothesis is analogous to reports in NERD, suggesting respiratory mucosal inflammatory disease could be the underlying mechanism in aspirin hypersensitivity .…”
Section: Discussionsupporting
confidence: 58%
“…Each trauma group was challenged 48 hours after injury with 0.5 to 1.0 Â 10 8 CFU of Pseudomonas intratracheally using a well-described nonsurgical model. 19,20 Figure 4 Substance P (SP) levels in naive mice or 30 minutes after tail trauma or mTBI. Mice were subjected to tail trauma or mild traumatic brain injury (mTBI) and sacrificed 30 minutes later, naive mice had no manipulation.…”
Section: Mtbi Specifically Enhances Resistance To Pneumoniamentioning
confidence: 99%
“…Therefore, the question was posed whether binge alcohol drinking could act as an asthma trigger in CRA-sensitized mice. Dr. Remick reported that a binge alcohol paradigm given to CRA-sensitized mice acted as an asthmatic trigger, increasing mucus production in the lung, hyper-reactivity, BAL inflammatory cell infiltrate, and elevated cytokine levels of IL-5, IL-13, and IL-4 in lung tissue homogenates just 30 min after gavage with alcohol (Bouchard et al, 2012). Binge alcohol consumption triggering an asthmatic episode was not found to be due to mast cell degranulation, but rather was due to increased leukotrienes production.…”
Section: Alcohol and The Lungmentioning
confidence: 99%